2015
DOI: 10.1021/acs.jpcc.5b05637
|View full text |Cite
|
Sign up to set email alerts
|

2D-IR Spectroscopy of Porous Silica Nanoparticles: Measuring the Distance Sensitivity of Spectral Diffusion

Abstract: Two-dimensional infrared spectroscopy (2D-IR) was used to investigate the sensitivity of a vibrational mode to spectral diffusion on the nanometer length scale. A confined volume within a porous silica nanoparticle was used as the model system. Utilizing a novel grafting technique, silane probes were covalently secured to the pore surface for a series of templated mesoporous silica nanoparticles with variable pore sizes. 2D-IR measurements determined that isopropanol exhibited two dominant time scales of ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
(118 reference statements)
2
17
0
Order By: Relevance
“…Further aging shows a decrease in Δ 1 with a concurrent rise in Δ 2 indicating transfer of these dynamics into a time regime that is too slow for our measurements to resolve. We recently reported a systematic study of spectral diffusion dynamics in templated silica nanoparticles with 3 to 12 nm pores and found a similar loss of faster dynamics in the FFCF as the pore sizes decreased . This is also consistent with nanoscopic solvent studies that have shown an overall slowing of solvent dynamics as the solvent pool dimensions decrease. , The pore sizes in the current work are in the 1–2 nm diameter regime, making it reasonable that the resolvable spectral diffusion time scale starts off even slower (∼6 ps).…”
Section: Results and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Further aging shows a decrease in Δ 1 with a concurrent rise in Δ 2 indicating transfer of these dynamics into a time regime that is too slow for our measurements to resolve. We recently reported a systematic study of spectral diffusion dynamics in templated silica nanoparticles with 3 to 12 nm pores and found a similar loss of faster dynamics in the FFCF as the pore sizes decreased . This is also consistent with nanoscopic solvent studies that have shown an overall slowing of solvent dynamics as the solvent pool dimensions decrease. , The pore sizes in the current work are in the 1–2 nm diameter regime, making it reasonable that the resolvable spectral diffusion time scale starts off even slower (∼6 ps).…”
Section: Results and Discussionsupporting
confidence: 88%
“…In a departure from this passive role, our group recently showed that a silicon hydride vibration on the silica surface could be used to probe the structural dynamics of molecular guests within the pore volume. 21,22 Rather than relying upon the spectroscopy of the infiltrating solvent or solute, or a chemically bound sensitizer, this approach transforms the silica matrix itself into a general sensing platform to monitor any infiltrating species.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have hypothesized previously that specific solvent-solute interactions with the oxygen atoms bound to a silicon site might be responsible for the enhanced solvatochromism in molecules such as TriMOS. 72,77 However, the FFCFs presented here for TriMOS, which has oxygen-bearing ligands, and TriPS, which lacks oxygen atoms, disprove this hypothesis since ν Si-H on both molecules senses the same dynamics. Recall that DFT calculations above showed that enhanced solvatochromism arises from increased coupling of ν Si-H to the reaction field due to mode polarization by the substituents.…”
Section: Resultsmentioning
confidence: 60%
“…Infrared absorption and Raman spectroscopies offer two approaches to characterizing the structure and inherent disorder of silicon surfaces. ,, Single crystal and amorphous silicon materials are commonly hydrogen-passivated to eliminate defects and improve their electronic properties . This results in surfaces that are covered with monohydride (R 3 Si–H) and polyhydride (R 2 Si–H 2 and RSi–H 3 ) vibrational modes that are sensitive to their local chemical environments. , Surface adsorption, desorption, and functionalization depend largely on the vibrational lifetime of these surface modes, , whose relaxation dynamics are often dominated by defects . Lyding and coworkers reported that hot electron degradation in silicon transistors was up to 50 times slower for deuterium-passivated surfaces, leading to enhanced carrier transport as a direct result of a shorter Si-D vibrational lifetime .…”
Section: Introductionmentioning
confidence: 99%